Effects of Biochar Feedstock and Pyrolysis Temperature on Soil Organic Matter Mineralization and Microbial Community Structures of Forest Soils - Lu, Xiaorong; Yin, Yan; Li, Shaopeng; Ma, Hongliang; Gao, Ren; Yin, Yunfeng (Frontiers in Environmental Science, 2021)
Biochar has received much attention as a strategy to enhance soil carbon (C) sequestration and mitigate climate change. Previous studies found that the feedstock and pyrolysis temperature can largely determine biochar properties, which in turn, impact the stability of native soil organic matter (SOM) and soil microorganisms. The Schima superba and Cunninghamia lanceolata are two tree species widely distributed in the subtropical region of southern China, but how the biochars from these two species influence the soil C sequestration and microbial communities of plantation remain poorly understood. In this study, we produced biochars from these two different feedstocks (13C-labeled S. superba and C. lanceolata litters) at three pyrolysis temperatures (350°C, 550°C, 750°C), then added them to the soils from C. lanceolata plantation, and maintained the experiments at 25°C for 112 d. We found both C mineralization and soil microbial community structures were strongly, but inconsistent, affected by biochar feedstock and pyrolysis temperature. The C. lanceolata biochar triggered the negative priming effect faster and greater compared with the S. superba biochar amendment. Biochars produced at 550°C showed the most significant negative priming effect during the whole incubation period, regardless of the different feedstocks. The cumulative amount of CO2 derived from biochars was significantly decreased with pyrolysis temperature (p < 0.05), indicating that biochars prepared at higher temperatures were more stable in the soil. Further, the soil microbial community structure was only affected by biochar pyrolysis temperature rather than biochar feedstock and their interaction. Together, our results reveal that biochar feedstock and pyrolysis temperature may play more important roles in dictating the priming effect than the structure of microbial community for C. lanceolata plantation. Overall, we concluded that the biochars prepared at 550°C could rapidly decrease the turnover of native SOM in a short term and has the potential to be a management practice for soil C sequestration in the C. lanceolata plantation.